The Planning of Weir Design for the Construction of Mini Hydro Power Plant in the Cirompang River, Cihikeu Village, Bungbulang, Garut Regency - Hardiyanti, Dini
The electricity needs of the Indonesian people continue to increase beyond the development of electricity generation infrastructure. To help meet national electricity needs, new and renewable energy sources (EBT) are needed as electricity generation, for example wind, water, and solar energy. The oldest and biggest source of EBT in Indonesia is hydroelectric power (PLTA). One of the potential locations to build a mini hydro power plant (PLTMH) is on the Cirompang River, Garut Regency. To create a good PLTMH, it is necessary to design a weir that serves to raise the river water level. Cirompang PLTM weir is located at coordinates 7o 27’ 1.21”S – 107o 36’ 32.22” E. A stand strong weir building must be supported by the strong upper and lower structure. Therefore, it is necessary to plan a detailed design to optimize the potential of existing water resources with hydrological analysis and hydraulic planning of the weir and the stability of the construction. Weir is planned with concrete material. The design plan discharge is 650.9 m3/s. The dimensions of Cirompang weir based on the calculation are as follows: the effective width of the weir is 38 meters, the length of the apron is 10 meters, the weir type is ogee with a lighthouse height of 5 meters from the apron, the stilling basin is a sinking type (bukcet) with a radius of 5 meters, weir downstream height is 4.3 meters. This design meets the requirements for stability against the dangers of rolling, sliding, eccentricity, and earthquake for both normal and flood water conditions. The budget plan includes work for the diversion channel, cover dams, the main building which is the weir, and the flushing building. The total planned budget is IDR 4,441,573,674.00.